2021
DOI: 10.6061/clinics/2021/e3036
|View full text |Cite
|
Sign up to set email alerts
|

CircularRNA_0119872 regulates the microRNA-582-3p/E2F transcription factor 3 pathway to promote the progression of malignant melanoma

Abstract: Malignant melanoma (MM) is an invasive tumor that poses a threat to patient health. Circular RNAs (circRNAs) are important regulators of MM carcinogenesis. In this study, we investigated the expression characteristics and biological functions of, and mechanism underlying, circ_0119872 expression in MM. METHODS: Quantitative reverse transcription-polymerase chain reaction (qRT-PCR) was employed to examine the circ_0119872, microRNA (miR)-582-3p, and E2F transcription factor 3 (E2F3) mRNA expression levels in MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Mechanistically, miRNAs usually were targeted by circRNAs and then regulated mRNA to influence melanoma progression. Circ_0119872 acted as a sponge for miR‐582‐3p, and E2F3 acted as a target gene of miR‐582‐3p, this axis promoted melanoma proliferation and metastasis 12 . Circ_0082835 upregulated EZH2 by targeting miR‐429 and promoted the development of melanoma 24 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mechanistically, miRNAs usually were targeted by circRNAs and then regulated mRNA to influence melanoma progression. Circ_0119872 acted as a sponge for miR‐582‐3p, and E2F3 acted as a target gene of miR‐582‐3p, this axis promoted melanoma proliferation and metastasis 12 . Circ_0082835 upregulated EZH2 by targeting miR‐429 and promoted the development of melanoma 24 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is growing evidence that circRNAs are important processes in cancer cell viability, metastasis, or glycolysis 7,8 . The involvement of circRNA in the pathogenesis of tumors including melanoma has become a hot topic 9–12 . For example, circ_0062270 regulated miR‐331‐3p/EPHA2 axis thus promoted melanoma development 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CircRNAs that have binding sites for miRNAs may act as sponges for miRNAs to play regulatory roles (Qu et al 2021). In addition, more and more studies had demonstrated that miRNAs regulated the expression of downstream target genes (Bi et al 2019;, and circRNAs further regulated the expression changes of downstream genes through miRNAs (Bi et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“… 74 In malignant melanoma, circ_0119872 encourages cell proliferation by relieving the inhibitory effect of miR-582-3p on E2F3 via sponging. 75 Another study reported that circAGAP1 (circ0058792) expression was significantly upregulated in clear cell renal cell carcinoma (ccRCC) tissues compared to that in adjacent non-tumor tissues. In particular, circAGAP1 played a carcinogenic role in ccRCC progression by regulating the miR-15-5p/E2F3 axis.…”
Section: Circrna-mediated Regulation Of Cell Cycle Via Prb-e2fsmentioning
confidence: 99%